Sexual harrassment and gender discrimination in the active-component army: variation in most serious event characteristics by gender and installation risk - Calkins, Avery; Cefalu, Matthew; Schell, Terry L.; Cottrell, Linda; Meadows, Sarah O.; Collins, Rebecca L. (Rand Corporation, 2021)
To better understand sexual harassment and gender discrimination in the Army, RAND Arroyo Center researchers created profiles of active-component soldiers' most serious sexual harassment and gender discrimination experiences. This report describes the most common types of behaviors that occur, characteristics of (alleged) perpetrators, most common times and places in which sexual harassment and gender discrimination occur, and differences between high-risk and non-high-risk installations. Women's and men's experiences of sexual harassment and gender discrimination look broadly the same at high-risk installations compared with non-high-risk installations, and they do not appear to differ across high-risk installations. However, men's and women's experiences of sexual harassment and gender discrimination in the active-component Army are very different. Women are more likely than men to experience gender discrimination, repeated attempts to establish an unwanted romantic or sexual relationship, and sexual comments about their appearance, whereas men are more likely than women to be told that they do not act like a man is supposed to act. Soldiers often experience multiple forms of sexual harassment and gender discrimination; women experience more types of behaviors, on average, than men do. What women's and men's experiences have in common is that they frequently take place at work during the workday and involve exposure to offensive or persistent discussion of and jokes about sex